The Sabah Oral Literature Project - Appell, George (World Oral Literature Project, 2010)
George N. Appell, M.B.A., A.M. (Harvard), Ph.D. (Australian National University) is a social anthropologist. He has done fieldwork, assisted by his wife Laura W.R. Appell, among the Dogrib Indians of the Northwest Territories of Canada, the Rungus of Sabah, Malaysia, and the Bulusu’ of Indonesian Borneo. They began working with the Rungus in 1959 to record their social organization, language, religion and cultural ecology. They continue to work with the Rungus and are compiling ‘The Rungus Cultural Dictionary’ as well as managing the Sabah Oral Literature Project. This project continues to collect the oral literature of the Rungus and other peoples of the Kudat Peninsula. Dr Appell is cofounder and president of the Borneo Research Council, founder and president of the Firebird Foundation for Anthropological Research, founder of the Anthropologists’ Fund for Urgent Anthropological Research, and is Senior Visiting Scholar in the Department of Anthropology, Brandeis University. He is currently finishing a monograph on culture-free methods to determine rights over resource tenure and other property interests that are faithful to the local distinctions. Other information on the publications of the Appells can be found at: www.gnappell.org George and Laura Appell were prevented by the Sabah government from continuing their research among the Rungus, which had begun in 1959-1963. But in 1986 they were permitted to return to the Rungus and visit their friends. By then little of the traditional Rungus social organization and culture remained unchanged, except for their oral literature. Consequently, George and Laura Appell formed the Sabah Oral Literature Project to collect the various genre from the Rungus and related ethnic groups. The project was so constructed as to be run by the Rungus for the Rungus, with the Appells providing equipment, direction and training. It was hoped that this project would form a model for ethnic groups in other areas of Sabah and in other regions of the world to begin collecting their ...